2021
DOI: 10.1186/s12935-021-01902-2
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0003288 induces EMT and invasion by regulating hsa_circ_0003288/miR-145/PD-L1 axis in hepatocellular carcinoma

Abstract: Background Epithelial-mesenchymal transition (EMT) has been associated with wound healing, tumorigenesis, and metastasis. Circular RNAs (circRNAs) are functional non-coding RNAs involved in multiple human cancers. However, whether and how circRNAs contribute to the EMT in hepatocellular carcinomas (HCC) remains to be deciphered. In this study, we investigated the regulation and function of hsa_circ_0003288 on programmed death-1 ligand 1 (PD-L1) during EMT and HCC invasiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The expression of hsa_circ_0000190 in lung cancer cells was transiently overexpressed or knocked down for 72 h. In total, 1–2 × 10 5 cells with 1% FBS medium were added in each insert, and 10% FBS medium was placed in each lower chamber. After 24 h of incubation at 37 °C, inserts were taken out and counted under an inverted fluorescent microscope [ 18 ]. The average number of cells and images from the microscopic fields of three experiments were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of hsa_circ_0000190 in lung cancer cells was transiently overexpressed or knocked down for 72 h. In total, 1–2 × 10 5 cells with 1% FBS medium were added in each insert, and 10% FBS medium was placed in each lower chamber. After 24 h of incubation at 37 °C, inserts were taken out and counted under an inverted fluorescent microscope [ 18 ]. The average number of cells and images from the microscopic fields of three experiments were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have reported the role of circRNAs in regulating the expression of PD-L1 through circRNA–miRNA–mRNA axis. A number of circRNAs, such as circBART2.2, hsa_circ_0136666, circ-keratin 6c, CDR1-AS, circ-VIM, hsa_circ_0003288, CircCHST15, circ-CPA4, hsa-circRNA-002178, and Circ_0000284 were shown to affect PD-L1 expression, leading to tumor immune escape in various types of cancers, including nasopharyngeal carcinoma, colorectal cancer, esophageal cancer, hepatocellular carcinomas (HCC), and lung cancer [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Our previous study discovered the correlation between hsa_circ_0000190 plasma level and PD-L1 level in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some circRNAs have been concerned because of their roles in liver cancer via sponging flexible regulators, miRNAs. Specifically, knockdown of circ-CSPP1 can suppress HCC development both in vitro and in vivo by upregulation of miR-493-5p and downregulation of HMGB1 [75], circ-CCND1 plays a cancer-promoting role by modulating the miR-497-5p/HMGA2 axis [76], circPUM1 could promote the development of HCC by up-regulating the expression of MAP3K2 via sponging miR-1208 [77], circRNA-5692 can sponge miR-328-5p to enhance DAB2IP expression, and the circRNA-5692-miR-328-5p-DAB2IP regulatory pathway inhibits the progression of HCC [78], circ_CDR1as up-regulates RAF1 expression via targeting miR-1287 and further regulates EMT pathway through MEK/ERK [79], circ_0091579 up-regulates the expression of TRIM27 by acting as a molecular sponge of miR-136-5p [80], and hsa_circ_0003288 enhances the expression of PD-L1 by acting as a sponge of miR-145 to promote EMT [81], migration and invasion of HCC cells, circ_0008194 acts as a sponge of miR-190a to promote AHNAK expression [82], and all of these promote EMT process and HCC proliferation and migration. In addition, circHPS5 upregulates the expression of HMGA2 by acting as a miR-370 sponge, thus accelerating the occurrence and proliferation of HCC tumors and promoting the migration of cancer cells through the EMT pathway.…”
Section: Circrna-associated Cerna Network In Liver Cancermentioning
confidence: 99%
“…In cancer research, Wang et al (2021) found that circBACH2 was up-regulated in triple-negative breast cancer. Xu et al (2021) thought that hsa_circ_0003288 involved in regulation of hepatocellular carcinoma. For CRC, Zhou et al (2020) proved circCAMSAP1 was significantly upregulated in CRC tissues.…”
Section: Introductionmentioning
confidence: 99%